AB-initio studies on the electronic properties of new ferroelectric materials based on bulk SnB03 (B=Ti, Zr) and super lattice SnZr03/SnTi03 with using density functional theory (DFT). / Muhamad Kamil Yaakob - Yaakob, Muhamad Kamil (2010)
The electronic band structure, density of states (DOS) and phonon vibration of perovskite S11BO3 (B=Ti, Zr) and super lattice SnZr03/SnTi03 investigated from first principles calculation using Density Functional Theory (DFT) within Local-density Approximation (LDA). Full geometry optimization of SnTi03, SnZr03 and super lattice SnZr03/SnTi03 provides a stable tetragonal structure relative to cubic one. The calculated energy gap in the band structure of SnTi03 and SnZr03 and super lattice SnZr03/SnTi03 is 0.966 eV, 1.691 eV and 1.089 eV respectively. Phonon dispersion curves and lattice dynamic of bulk SnTi03 and SnZr03 is evaluated and found that these compounds having possibilities to transform into the lowest symmetry phase which are tetragonal, orthorhombic and rhombohedral below its Curie temperature (Tc). The born effective charges shows large charges between Sn-0 bond refers the strong electronic interaction (Coulomb interaction) along the bond and is also a factor that resulting ferroelectricity’s in the compound